Perspectivas de enseñanza de español como Lengua Extranjera en publicaciones académicas de 2000 a 2020 (2020)
In this monograph a bibliographic analysis of the processes and tendencies of the didactics of Spanish as a foreign language (ELE) is carried out, taking as a reference for its development various investigations and studies (academic reflections) carried out during the period from 2000 to 2020. This text presents a review, by way of analysis, which seeks to understand and identify trends in the teaching of Spanish as a foreign language in the last twenty years. In this way, the main perspectives, approaches and gaps that are part of the ELE teaching processes are established